2007
DOI: 10.1002/hed.20577
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radiotherapy with or without chemotherapy on tongue strength and swallowing in patients with oral cancer

Abstract: Parallel but not significant changes in oral intake, diet, and tongue strength in the first year post chemoradiation therapy need further study in a larger population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 22 publications
5
88
0
6
Order By: Relevance
“…16 However, recovery may never be complete. We and others have previously reported that 8% to 20% of long-term survivors may become G-tube dependent.…”
mentioning
confidence: 99%
“…16 However, recovery may never be complete. We and others have previously reported that 8% to 20% of long-term survivors may become G-tube dependent.…”
mentioning
confidence: 99%
“…In the CRT group there were statistical trends observed for more deficits in lingual control and increased aspiration risk on thin fluids, possibly due to the potential sequelae of the addition of chemotherapy to conventional radiotherapy. Late effects of CRT treatment have been reported to include chronic fibrosis resulting in stiffening of the tongue and hyolaryngeal complex [14], reduced glottic closure and oesophageal stenosis [34], that leads to significant oropharyngeal residue and aspiration. Indeed, a systematic review by van der Molen [35] found that chemoradiation regimens were associated with an increased aspiration rate, and this may result from the toxic effect on the neuromuscular junctions causing generalised weakness, fatigue, and sensory changes [36].…”
Section: Resultsmentioning
confidence: 99%
“…Although improving locoregional control and overall survival in [10], toxicity related to concurrent CRT regimens has been found to be significantly higher when compared to standard radiotherapy [1,11], and severe late swallowing complications have been found in 30-50% of patients treated with aggressive CRT regimens [4,11]. Reported dysphagia symptoms in HNC patients who received chemoradiotherapy regimens are diverse and have affected the oral phase [12][13][14], pharyngeal and upper esophageal phases of swallowing [12,13,15,16]. The impact on nutritional outcomes has been reported [5,12,15,[17][18][19], with several studies finding weight loss and nutritional compromise during and following radiotherapy and CRT protocols [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…2,9,[14][15][16][17] Decreased tongue mobility and strength, impairment in bolus preparation and transport, increased oral residue were described as oral phase disorders. 15,18,19 Delayed triggering swallowing reflex, impairment in velopharyngeal closure, decreased tongue base retraxion, pharyngeal contraction, hyolaryngeal elevation, airway closure, upper esophageal sphincter (UOS) opening and increased residue in tongue base, vallecula, pharynx and pyriform sinus were determined as phryngeal disorders after RT. 3,14,15,[20][21][22][23] In a study, decreased tongue base retraxion and hyolaryngeal elevation 1 month after CRT, delayed triggering swallowing reflex, impairment in airway closure 3 months after CRT, decreased UOS opening 6 and 12 months after CRT were found.…”
Section: Discussionmentioning
confidence: 99%